EFEKTIVITAS METODE PEMBELAJARAN TALK ACTION YOUR OBLIGATE (TAYO) TERHADAP PENINGKATAN KEAKTIFAN BELAJAR QUR’AN HADIS PESERTA DIDIK - Makmur (Musawa: Journal for Gender Studies, 2023)
Students' engagement can be enhanced when educators employ appropriate teaching methods during the learning process. Therefore, this study aims to uncover the levels of student engagement before and after the implementation of the Talk Action Your Obligate (TAYO) teaching method and to assess the effectiveness of the TAYO teaching method in increasing students' engagement in learning Qur'an Hadith. The research design used in this study is experimental, with a quantitative descriptive research method. The results of the research reveal that the Talk Action Your Obligate (TAYO) teaching method is effective when used in the Qur'an Hadith learning process, as it places learners at the center of the learning experience, thus encouraging them to actively develop their potential, provided that educators effectively guide the learning process. Furthermore, students' engagement in various indicators significantly improves following the implementation of the TAYO method. Hence, it is recommended for educators to consider using this method to prevent student boredom during the learning process.